Fatigue crack growth analysis of welded bridge details (Fracture and Structural Integrity, 2022)
The paper investigates the fatigue crack growth in typical bridge weldments by means of numerical analysis. The extended finite element (XFEM) method is coupled with the low-cycle fatigue (LCF) approach in ABAQUS, and parametric analyses are carried out in order to assess the influence of the main sample/testing features on the fatigue life of the investigated structures. The numerical results are found to be robust and reliable by performing comparisons with past experimental data and regulation design correlations.
Keywords: crack growth; fatigue; welded details; XFEM; ABAQUS